The causal relationship between ICT and FDI - Roghieh Gholami; Sang-Yong Tom Lee; Almas Heshmati (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper investigates the simultaneous causal relationship between investments in information and communication technology (ICT) and flows of foreign direct investment (FDI), with reference to its implications on economic growth. For the empirical analysis we use data from 23 major countries with heterogeneous economic development for the period 1976–99. Our causality test results suggest that there is a causal relationship from ICT to FDI in developed countries, which means that a higher level of ICT investment leads to an increase inflow of FDI. ICT may contribute to economic growth indirectly by attracting more FDI. Contrarily, we could not find significant causality from ICT to FDI in developing countries. Instead, we have partial evidence of opposite causality relationship. The inflow of FDI causes further increases in ICT investment and production capacity.
Keywords: C23; C33; C51; E22; F21; 330; foreign direct investment; information and communication technology; stationarity; cointegration; causality; LSDV; 2SLS; Direktinvestition; Informationstechnik; Wirtschaftswachstum; Entwicklungsländer